PENGEMBANGAN REST API SISTEM UIIADMISI DENGAN MENGGUNAKAN PENDEKATAN DOMAIN DRIVEN DESIGN - Muhammad Fachri Ramadhan; Zainudin Zukhri (JURNAL ILMIAH INFORMATIKA, 2023)
Student admission program is an event carried out by a higher education institution to accept new students every new academic year. UIIAdmisi system is a web-based admission information system that is used to digitize the implementation of the student admissions program at the Islamic University of Indonesia. This system has been used by the organizers of the Indonesian Islamic University student admissions program from 2016. During its use period, new developers experienced difficulties in developing the back-end side of the UIIAdmisi system because the code in the system was difficult to understand. One of the reasons why the UIIAdmission system is difficult for new developers to understand is because UIIAdmisi solves complex business processes, but the system is built on a monolithic architecture which makes it the code to be bloated. For this reason, the UIIAdmisi system architecture migration process was carried out from monolithic to microservices by separating the existing components of the system into small independent components. These small components will communicate via the HTTP protocol with the implementation of the REST interface. The system will also be designed using the Domain Driven Design approach to make it easier for new developers to understand.